Kearifan Lokal Markusip Hakikat Pergaulan Muda Mudi Etnis Mandailing Tempo Dulu Sebelum Menuju Jenjang Pernikahan - Lenni Ertati, Lenni Ertati; Saefur Rochmat (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2023)
Markusip means the approach that is made between men and women by whispering from behind the walls of the house. The emergence of markusip local wisdom in Mandailing land cannot be separated from the influence of Islamic religious teachings brought by the priest troops which changed all aspects of the life of the Mandailing people, including in terms of association. The purpose of this writing is to describe the implementation of markusip local wisdom carried out by youth of the Mandailing ethnicity in the past before heading to marriage. The method used in this paper is descriptive qualitative method through literature studies both through books, journals, theses and other scientific articles. The results of this study indicate that the local wisdom of markusip is a manifestation of the implementation of the Islamic religionwhich prohibits interaction between men and women who are not mahrams. So that in practice both men and women cannot see each other because they are limited by the walls of the house. The local wisdom of markusip is a vessel for marriage if there is compatibility between men and women.